NA-ALGINATE BEADS OF CALCIUM / IRON-LAYERED DOUBLE HYDROXIDE FOR TREATING WATER CONTAMINATED WITH AMOXICILLIN ANTIBIOTIC - Marwa F. Abed,; Ayad A.H. Faisal, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The objective of this study was to prepare an adsorbent material from eggshells of chicken banished to the ambient as wastes to satisfy the ecological requirements of sustainable. The preparation process based on the extraction of calcium ions from eggshells and these ions must be reacted with iron to form nanoparticles of (Ca/Fe)-layered double hydroxides (LDHs) which immobilized as Na-alginate beads. Molar ration of calcium to iron, pH and dosage of LDH nanoparticles must be equal to 1, 12 and 5 g/100 mL to ensure that the prepared beads have highest ability to remove of Amoxicillin (AMOX) antibiotic with removal efficiency equal to 32% for operational conditions of Co=100 mg/L, beads dosage=0.5 g/50 mL, speed=200 rpm, pH=7 for 3 hrs. To increase this efficiency to ≥ 90%, best conditions must be time 90 min, pH 7, and beads mass 1.2 g/ 50 mL for Co 100 mg/L at 200 rpm in the batch mode. The Pseudo second order has high capability in the description of such tests with coefficient of determination (R2) ≥ 0.9924 and sum of squared error (SSE) ≤ 0.1287. Hence, the sorption of AMOX onto beads is governed by the chemisorption process. The reflections of XRD analysis proved the presence of (Ca/Fe)-LDH nanoparticles with size of 13.49 nm, calcium hydroxide (Ca(OH)2) and calcium carbonate (CaCO3)